Government Wilayah Al-Faqih in Iran and Contemporary Global Challenges - Hojjatollah Ebrahimian (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2020)
Today, despite all pressures and sanctions of the global politic, the Islamic Revolution of Iran has its own place in the hearts of freedom seeking people all over the world and every day, its progress and grandeur is improving. Therefore, progress of Islamic Iran during the last four decades is not something covered to all people and declaring these challenges across the society will lead to hopefulness and increase of resistance of people against these plots. Discussing the challenges of the Islamic Revolution and picturing them is a great and basic necessity of the present time. Therefore, this paper tends to clarify the most important challenges of the Islamic Revolution of Iran, from the very beginning to the present time, under the Islamic government based upon the Government of Wilayah Al-Faqih. On the contrary of propaganda of the enemies of the Islamic government, Islamic Revolution of Iran has faced great and eye catching progress in political, cultural, economic, scientific, technological, military, and intelligence areas despite all obstacles and limited facilities and now has reached a high position throughout the region and the world.